The public awareness level of the potential of developing solar energy projects for solving energy issues of flood areas in Kota Bharu, Kelantan / Mohamad Izzul Ismat Amran and Nur Azfahani Ahmad - Amran, Mohamad Izzul Ismat; Ahmad, Nur Azfahani (2023)
This research aims to assess public awareness of solar energy development in flood areas in Kota Bharu, Kelantan.. In cases like natural disaster, for instance flood disaster, solar energy is very significant during flooding in Kelantan 2014 it was created a devastating phenomenon for city dwellers. Energy consumption rises along with economic expansion since there is a proportionate relationship. Even though numerous methods for boosting energy production capacity have been suggested, many people in developing nations continue to live in places that lack electricity, especially during flood disaster that have issues on electricity supply .The research aims to measure public awareness levels towards solar energy development in flood areas. The primary data is a survey questionnaire with 200 respondents from flood areas in Kota Bharu, Kelantan, while secondary data is collected from various sources, including Google Scholar, research gate, research paper, book, official website, journal, and newspaper. The findings suggest that many respondents have a solid understanding of the solar system and are accepting of its use. The solar energy project is well-aware and widely accepted, particularly in aiding people in obtaining alternative energy during floods.